2020
DOI: 10.1194/jlr.r120000800
|View full text |Cite
|
Sign up to set email alerts
|

Roles of polyunsaturated fatty acids, from mediators to membranes

Abstract: Polyunsaturated fatty acids (PUFAs), such as arachidonic acid and docosahexaenoic acid, are recognized as important biomolecules, but understanding their precise roles and modes of action remains challenging. PUFAs are precursors for a plethora of signaling lipids, for which knowledge about synthetic pathways and receptors has accumulated. However, due to their extreme diversity and the ambiguity concerning the identity of their cognate receptors, the roles of PUFA-derived signaling lipids require more investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 115 publications
1
77
0
Order By: Relevance
“…Omega-3 long-chain polyunsaturated fatty acids (LC-PUFAs) exert antiangiogenic and neuroprotective functions in the retina ( 6 ). The LC-PUFA docosahexaenoic acid (DHA) plays a pivotal role in photoreceptor development and maintenance ( 7 , 8 ). High intake of eicosapentaenoic acid (EPA) and DHA has been shown to prevent or delay intermediate age-related macular degeneration.…”
mentioning
confidence: 99%
“…Omega-3 long-chain polyunsaturated fatty acids (LC-PUFAs) exert antiangiogenic and neuroprotective functions in the retina ( 6 ). The LC-PUFA docosahexaenoic acid (DHA) plays a pivotal role in photoreceptor development and maintenance ( 7 , 8 ). High intake of eicosapentaenoic acid (EPA) and DHA has been shown to prevent or delay intermediate age-related macular degeneration.…”
mentioning
confidence: 99%
“…DHA is derived from ALA through the enzymatic biosynthesis; ALA along with its omega-6 counterpart LA must be obtained from the diet because the human body is unable to synthesize them. PUFAs have shown to exert pleiotropic effects on cell membranes and to play a crucial role for the regulation of membrane biophysical properties, particularly as lipid mediator precursors and membrane components especially n-3 PUFAs [ 2 , 3 ]. DHA has demonstrated consistent beneficial healthy effects, including anti-inflammatory, antiproliferative, antiangiogenic, and antioxidant properties [ 4 , 5 , 6 ], as well as a critical involvement on underlying mechanisms of fetal neurodevelopment and immune function of newborns [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that besides their quantity, the qualities of fatty acids (e.g., saturated fatty acid toxicity and omega-3/omega-6 fatty acid balance) are involved in various human diseases, including metabolic syndrome, inflammatory diseases, and neuronal diseases ( Bazinet and Laye, 2014 ; Estadella et al., 2013 ). Especially, omega-3 polyunsaturated fatty acids (PUFAs), such as docosahexaenoic acid (DHA), and omega-6 PUFAs, including arachidonic acid (ARA), are implicated in diverse cellular processes and in the progression of these diseases as bioactive lipid mediators, or as components of membrane phospholipids (PLs) ( Harayama and Shimizu, 2020 ; Jump et al., 2013 ; Milligan et al., 2017 ; Shimizu, 2009 ; Wang and Tontonoz, 2019 ). PUFA-containing PLs are supposed to affect the membrane-based cellular processes, such as endo/exocytosis, and localization and functions of a number of membrane proteins by providing fluidity to the cellular membrane ( Antonny et al., 2015 ; Harayama and Riezman, 2018 ).…”
Section: Introductionmentioning
confidence: 99%